کوردستان لە نێوان سایکس- پیکۆی کۆن و نوێ دا لێکۆڵینەوەیەک لە جوگرافیای ڕامیاری دا - تالیب, جه‌زا تۆفیق; كریم, أحمد ڕفیق; محمد, شاد حمید (Sulaimani Journal for Humanities, 2018)
Kurdistan geographically between the Sykes-Picot old and new One hundred years ago the grate world colonialism divided the western Kurdistan part to three small parts in the secret agreement and they put each part to the new state border, the new states have being genocide Kurdish people and destroyed Kurdistan . Some parts of Sykes –picot agreement area, has become a stadium among the new and some old grate player state computation in the world since2011, to showing dominance and economic, political, geographical, military… conflicts, it’s time to new redraw the middle east border, Kurdish rights and earn (political, economic, geographic…) in any future agreements in the this area pegged to the union and cooperation between Kurdish people and exploit all opportunities.